2017
DOI: 10.1111/een.12385
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoids override a parasite exposure impact on hibernation success of a key bumblebee pollinator

Abstract: Abstract. 1. Seasonal adaptations enabling the bridging of periodic challenging abiotic conditions are taxonomically widespread. However, sensitivity to other environmental stresses can be heightened during these periods.2. Several temperate insects with over-wintering strategies play key ecosystem and economic roles, including wild bee pollinators. For example, hibernation survival in temperate bumblebees is crucial, as only new queens of future social colonies over-winter. These bees are also faced with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 73 publications
3
62
2
Order By: Relevance
“…B 285: 20180761 exposure levels in some landscapes. Our study is one of a small but growing number of studies examining the unique effects of neonicotinoid exposure on the solitary life-history stages of bumblebee queens [36,39,40,69]. Collectively, these studies suggest that there are unique deleterious effects on queens that can have dramatic consequences for reproduction and nesting success.…”
Section: Discussionmentioning
confidence: 89%
“…B 285: 20180761 exposure levels in some landscapes. Our study is one of a small but growing number of studies examining the unique effects of neonicotinoid exposure on the solitary life-history stages of bumblebee queens [36,39,40,69]. Collectively, these studies suggest that there are unique deleterious effects on queens that can have dramatic consequences for reproduction and nesting success.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies have focused on the reproductive potential of worker bees in queenless colonies, and worker fecundity in queenright colonies (Laycock et al 2012(Laycock et al , 2013Whitehorn et al 2012); however, little has been researched on the direct impacts on queen bumble bees. More recent work has shown adverse effects on hibernation success, ovary development, and fecundity in Bombus terrestris (L.) (Hymenoptera: Apidae) queens exposed to the neonicotinoid, thiamethoxam (Baron et al 2017, Fauser et al 2017. Baron et al (2017) also showed species-specific responses to thiamethoxam consumption and toxicity in four different bumble bee species (Bombus terrestris, Bombus lucorum (L.), Bombus pratorum (L.), and Bombus pascuorum (L.) (Hymenoptera: Apidae)), which highlights the need for more information about the potential impacts on other bumble bee species.…”
mentioning
confidence: 99%
“…Each spring, solitary queen bumble bees face thermoregulatory challenges as they emerge from hibernation to establish new colonies. This is also the stage of the life cycle at which C. bombi can be most virulent (Brown et al, 2003;Fauser et al, 2017). The availability of adequate early season floral resources may be a key determinant of the ability of queens to maintain body temperatures necessary for foraging, brood incubation and parasite inhibition.…”
Section: Resource Availability Could Alter Thermoregulation In Wild Beesmentioning
confidence: 99%